Biofabricated Fatty Acids-Capped Silver Nanoparticles as Potential Antibacterial, Antifungal, Antibiofilm and Anticancer Agents - Mohammad Azam Ansari; Sarah Mousa Maadi Asiri; Mohammad A. Alzohairy; Mohammad N. Alomary; Ahmad Almatroudi; Firdos Alam Khan (MDPI AG, 2021)
The current study demonstrates the synthesis of fatty acids (FAs) capped silver nanoparticles (AgNPs) using aqueous poly-herbal drug Liv52 extract (PLE) as a reducing, dispersing and stabilizing agent. The NPs were characterized by various techniques and used to investigate their potent antibacterial, antibiofilm, antifungal and anticancer activities. GC-MS analysis of PLE shows a total of 37 peaks for a variety of bio-actives compounds. Amongst them, n-hexadecanoic acid (21.95%), linoleic acid (20.45%), oleic acid (18.01%) and stearic acid (13.99%) were found predominately and most likely acted as reducing, stabilizing and encapsulation FAs in LIV-AgNPs formation. FTIR analysis of LIV-AgNPs shows some other functional bio-actives like proteins, sugars and alkenes in the soft PLE corona. The zone of inhibition was 10.0 ± 2.2-18.5 ± 1.0 mm, 10.5 ± 2.5-22.5 ± 1.5 mm and 13.7 ± 1.0-16.5 ± 1.2 against P. aeruginosa, S. aureus and C. albicans, respectively. LIV-AgNPs inhibit biofilm formation in a dose-dependent manner i.e., 54.4 ± 3.1%-10.12 ± 2.3% (S. aureus), 72.7 ± 2.2%-23.3 ± 5.2% (P. aeruginosa) and 85.4 ± 3.3%-25.6 ± 2.2% (C. albicans), and SEM analysis of treated planktonic cells and their biofilm biomass validated the fitness of LIV-AgNPs in future nanoantibiotics. In addition, as prepared FAs rich PLE capped AgNPs have also exhibited significant (p < 0.05 *) antiproliferative activity against cultured HCT-116 cells. Overall, this is a very first demonstration on employment of FAs rich PLE for the synthesis of highly dispersible, stable and uniform sized AgNPs and their antibacterial, antifungal, antibiofilm and anticancer efficacy.